2021
DOI: 10.1093/brain/awab113
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel increases axonal localization and vesicular trafficking of Nav1.7

Abstract: The microtubule-stabilizing chemotherapy drug paclitaxel (PTX) causes dose-limiting chemotherapy-induced peripheral neuropathy (CIPN), which is often accompanied by pain. Among the multifaceted effects of PTX is an increased expression of sodium channel NaV1.7 in rat and human sensory neurons, enhancing their excitability. However, the mechanisms underlying this increased NaV1.7 expression have not been explored, and the effects of PTX treatment on the dynamics of trafficking and localization of NaV1.7 channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 47 publications
4
41
1
2
Order By: Relevance
“…In the transcriptomic analysis, we demonstrated significant upregulation of MMP24 which mediates peripheral thermal nociception and inflammatory hyperalgesia [ 55 ]. While the mechanism of upregulated MMP24 in the face of SBF2 is not completely elucidated, our functional data would support the possibility of causing hypoexcitability through changes in the number of neuronal ion channels on the surface or vesicular trafficking [ 48 51 ]. In addition, SLC7A11 which increases resistance to oxidative stress [ 56 , 57 ] and in integrated in the inflammatory response pathway, was the only significantly down-regulated gene in paclitaxel-treated si SBF2 cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the transcriptomic analysis, we demonstrated significant upregulation of MMP24 which mediates peripheral thermal nociception and inflammatory hyperalgesia [ 55 ]. While the mechanism of upregulated MMP24 in the face of SBF2 is not completely elucidated, our functional data would support the possibility of causing hypoexcitability through changes in the number of neuronal ion channels on the surface or vesicular trafficking [ 48 51 ]. In addition, SLC7A11 which increases resistance to oxidative stress [ 56 , 57 ] and in integrated in the inflammatory response pathway, was the only significantly down-regulated gene in paclitaxel-treated si SBF2 cells.…”
Section: Discussionmentioning
confidence: 85%
“…The presence of inflammatory mediators has also been shown to affect vesicular trafficking of ion channels, thereby affecting the neuron’s response to stimuli [ 48 51 ]. Our transcriptomic data indicated that the inflammatory mediator MMP24 was significantly up-regulated ( Fig 6B ) and inflammatory pathways were enriched in paclitaxel-treated si SBF2 cells ( S1 Fig ), but not in the paclitaxel-treated control cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have just mentioned that PTX promotes Na + channel insertion into the surface membrane [229], which correlates with PTX-induced increased levels of endogenous Nav1.7 mRNA levels and Na + current density [230]. Thus, the changes in ion channels induced by PTX [229,230] could be the cause of the non-convulsive status epilepticus, revealed by EEG, induced by chemotherapeutic administration of PTX [231].…”
Section: Changes In Excitability and Synaptic Transmission And Their ...mentioning
confidence: 95%
“…Na v 1.7 is found in both sensory and sympathetic nerve fibers, might Na v 1.7 blockers be especially useful in complex regional pain syndromes? By contrast, in animal studies Na v 1.7 does not appear to be involved in oxaliplatin-induced painful neuropathy (123) yet does appear to be involved in that seen with paclitaxel (154). Does this mean that Na v 1.7 blockers might only be effective in subgroups of patients with chemotherapy induced neuropathy (CIPN)?…”
Section: Think About Sexmentioning
confidence: 98%